Digital Evaluation of Three Splinting Materials Used to Fabricate Verification Jigs for Full‐Arch Implant Prostheses: A Comparative Study. Issue 2 (21st October 2016) - Papaspyridakos, Panos; Kim, Yong‐Jeong; Finkelman, Matthew; El‐Rafie, Khaled; Weber, Hans‐Peter
Abstract: Purpose: The primary aim of this study was to assess the accuracy of different splinting materials to make implant cast verification jigs. The secondary aim was to assess the effect of 20° implant angulation on the accuracy of casts. Materials and Methods: An edentulous mandibular arch with five internal connection tissue level implants served as control. The three implants in the anterior region were parallel to each other and the two implants in the posterior region were distally tilted 20° bilaterally. Verification jigs were fabricated with three different materials by splinting prefabricated bars to temporary abutments, resulting in three different groups ( n  = 15 specimens). Test casts were fabricated with low expansion type IV stone, and subsequently digitized with reference scanner. The STL files from the test casts and the control were superimposed, in order to determine the three‐dimensional (3D) deviations. Results: Group 1 (GC Pattern Resin) had a mean (SD) value of 36.59 (12.47) μm; Group 2 (Fixpeed Resin) had a mean (SD) value of 35.9 (10.13) μm; and Group 3 (Triad Gel) had a mean (SD) of 34.12 (7.10) μm. One‐way ANOVA showed no statistically significant difference between groups ( p  = 0.790). For the comparative analysis of the effect of implant angulation, data were normally distributed for Groups 1 and 3 (GC Resin and Triad Gel), but not for group 2 (Fixpeed Resin). The difference between parallel and tilted implants was significant for all three groups: GC Resin ( p  = 0.024; paired t ‐test), Fixpeed Resin ( p  = 0.002; Wilcoxon signed‐rank test), and Triad Gel ( p  = 0.002; paired t ‐test). Conclusions: There were no statistically significant differences between the 3D deviations of the test casts fabricated from verification jigs made by three materials (GC Pattern Resin, Fixpeed Resin, and Triad Gel). Parallel implants had nominally significantly less 3D deviations compared with 20° distally tilted implants, but not clinically significant. Clinical Significance: The results of the present study indicate that more than 20° of angulation, has an effect on the 3D accuracy. However, even though the tilted implants had nominally significantly more 3D deviation, it was not clinically significant. The clinical implications of this in vitro study are relevant to the popular full‐arch implant rehabilitation concept of tilted and axial implants such as the All‐on‐four concept. Tilting the posterior implants to increase the antero‐posterior spread increases the implant angulation which is then corrected with 30° angulated abutments. This in vitro study shows that even after correction with angulated abutments if the remaining angulation is up to 20°, framework fit may still be achieved. Verification jig is essential tool to achieve the framework fit. (J Esthet Restor Dent 29:102–109, 2017)